Supporting the EU with(out) Political Knowledge: Empirical Evidence from a New Joiner - Sergiu Gherghina (Romanian Journal of European Affairs, 2010)
This article investigates the relationship between political knowledge and trust in the EU among the Romanian citizens between 2002 and 2009. It uses individual level data from the Candidate Countries (2001-2004) and Standard Eurobarometers (2005-2009) to check whether there is a direct linkage between the decreasing level of trust and the increasing level of knowledge in the most Euro-optimist new member state. The statistical analysis reveals that the more citizens know about the EU, the more they trust it. Such a result gains supplementary relevance in the context of decreasing support. Two other general results are relevant for the Romanian case. First, although the level of political knowledge increases as the accession gets closer, it continues to be quite low. Second, the Romanian citizens constantly overestimate their knowledge about the EU.